Kajian Survei: Isu Kemampuan Komunikasi dan Ketahan Mental Santri Dhuafa Sepanjang Pandemic Covid -19 di Kabupaten Bogor - Anggrayni, Dewi; siregar, Nur Choiro (Universitas Djuanda Bogor, 2022)
Communication skills are the main indicator in the success of building social relations in the community. However, the presence of the COVID-19 pandemic over the past two years has had an impact on society. Social restrictions are one of the reason for the limited interaction and communication of a dynamic society. The school environment is one institution that has received the impact of this pandemic. Children and teachers must carry out teaching and learning activities through the Distance Learning (PJJ) method. This survey study will discuss how santri dhuafa can maintain mental resilience with healthy communication skills. Among the effects that are strongly felt due to the lack of interactive communication between teachers and students is psychological pressure. The pressure with this PJJ activity causes students to have difficulty doing the tasks given by the teacher. Facilities such as the unavailability of an internet connection increasingly interfere with learning, especially for students who are in the interior. The worst result is that children are no longer interested in participating in learning to the fullest. For students with poor economic conditions, this situation will be even more difficult. An unstable economy increases the power of students as well, this situation is often one of the other triggers that have an impact on students mental resilience as specialiy in Bogor Area. communication skills become an important part for students in its difficult situation to catching up learning.